Pelatihan Penggunaan Pelayanan Online Administrasi Kependudukan (Aplikasi GRATIS KABEH) bagi Ibu PKK Desa Beji - Ito Setiawan; Retno Waluyo; Dewi Fortuna; Intan Indri Fitriani (Madani : Indonesian Journal of Civil Society, 2022)
DINDUKCAPIL Banyumas has implemented the “GRATIS KABEH” application. This application provides convenience and transparency for the people of Banyumas Regency to report population events easily, effectively and efficiently without having to queue. In using the Gratis Kabeh application, many people still do not know about online services. People have to wait for hours for population data administrators, this is a new problem, especially now that it is still during the COVID-19 pandemic. From these problems, it is necessary to provide training on how to use the Gratis Kabeh application to PKK women in Beji Village so that people can take advantage of online services to manage occupation data. The training method uses presentations, practicums and discussions. The result of this training is that PKK Beji Village women can use the Gratis Kabeh application to manage population data.